Design and fabrication of UMP go-kart chassis - Lim, Wai Tuck (2007)
Go-kart has become more and more popular sport in these days and Go-kart chassis have made a major development over the last few years. The performance of a Go-kart is depends a lot on the chassis design. A good chassis needs to be able to flex and twist. Thus, this project takes a look at the investigation of chassis design, simulation and fabrication. The first criteria have to be consider is that would be certain amount of flexing in the chassis but not too much that would reduce the strength of the kart. Therefore, the design will focused on the front end and the middle section of the chassis. In order to ensure that the design of the chassis achieve the standard level. Type of simulation used is Finite Element Analysis (FEA) by using COSMOSWork 2004. The purpose of this simulation was implementing to investigate the strength and the flexibility of the chassis. The simulations carried out with several altered parameters for flexibility investigation. The maximum stress of all cases are normally acting upon at the point of the bending parts but the value is under the maximum allowable stress of mild steel which is 420 MPa and achieved the factor, of safety as well. Fabrication process including three processes, there are cutting process by using rotary disc cutter, bending process by using manually hydraulic bender and welding process by using MIG welder.